Education and Research Policy as an Instrument of Soft Power in Germany - N. Bolshova (Vestnik MGIMO-Universiteta)
Paper analyzes higher education and resarch policy in Germany as an important instrument in ensuring the competitiveness and influence of the state in the international arena. In today's global struggle for leadership Germany relies on "soft" and "smart" power («soft and smart power»): education, research, innovation and human capital. This article discusses the most important initiatives the federal government and lands in the past five years, aiming at strengthening the position of Germany as a world center of higher education and advanced research and the most attractive location for highly qualified specialists from around the world.